Evaluate the expression when y = -5.

y^2+6y-9

1 answer

To evaluate the expression \( y^2 + 6y - 9 \) when \( y = -5 \), we substitute \(-5\) for \(y\):

\[ y^2 + 6y - 9 = (-5)^2 + 6(-5) - 9 \]

Now, let's calculate each term:

  1. Calculate \((-5)^2\): \[ (-5)^2 = 25 \]

  2. Calculate \(6(-5)\): \[ 6(-5) = -30 \]

Now, substitute these values back into the expression:

\[ 25 - 30 - 9 \]

Next, simplify it step by step:

  1. \(25 - 30 = -5\)
  2. Now, \(-5 - 9 = -14\)

Thus, the value of the expression when \( y = -5 \) is:

\[ \boxed{-14} \]